A qualitative study on teachers' perceptions of their learners' mental health problems in a disadvantaged community in South Africa - Donald Skinner; Carla Sharp; Lochner Marais; Motsaathebe Serekoane; Molefi Lenka (AOSIS, 2019)
Background: The combination of extensive poverty, violence and HIV has potential mental health impacts on children in Southern Africa. This article is nested in a broader study to evaluate the strength and difficulties questionnaire (SDQ) among Sotho speakers, and assess the mental health status of children made orphans by AIDS. Objectives: The aim of this study was to describe the mental health problems that the teachers perceive among learners in their classrooms, to understand what the teachers saw as causing these problems and to identify potential approaches to address these problems within the school setting. Method: As part of the larger study, 10 teachers were purposively selected to write a report describing the mental health problems among learners in their class. These findings were discussed at two later meetings with a larger grouping of teachers to validate the findings and obtain additional input. Results: The teachers were concerned about the emotional state of their pupils, especially in relation to depression, anxiety, substance abuse, scholastic problems and aggression. These problems were felt to arise from the children's lived context; factors such as poverty, death of parents and caregivers from AIDS and trauma, parental substance abuse and child abuse. The teachers expressed a desire to assist the affected learners, but complained that they did not get support from the state services. Conclusion: Many learners were evaluated by teachers as struggling with mental health issues, arising from their social context. The teachers felt that with support, schools could provide assistance to these learners.